Paternal inheritance of translocation chromosomes in a t(X;21) patient with X linked muscular dystrophy. Issue 6 (December 1986) - Kean, V M; Macleod, H L; Thompson, M W; Ray, P N; Verellen-Dumoulin, C; Worton, R G
Abstract : A number of DNA probes from the short arm of the X chromosome have been used to study the inheritance of the translocation chromosomes in a girl with an X; autosome translocation and muscular dystrophy. The two translocation chromosomes were found to be derived from the father's single normal X chromosome, ruling out maternal inheritance of a pre-existent mutation and enhancing the concept that the de novo translocation is responsible for the dystrophic phenotype.